THE COMPREHENSIVE SYSTEMATIC REVIEW OF NEUTROPHIL GELATINASE–ASSOCIATED LIPOCALIN AS A PREDICTOR OF PRE-ECLAMPSIA - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina; Whisnu Dewanegara, Rahadiyan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The use of NGAL for preeclampsia and eclampsia prediction looks appealing, but one has to understand that NGAL levels increase in the state of inflammatory conditions associated with epithelial cell injury like pelvic inflammatory disease, chronic obstructive pulmonary disease, malignancies of breast, lungs, and colon. NGAL is also released from maternalfetal interface and is thought to be released when there is uterine vasoconstriction as happens in preeclampsia. The aim: This study aims to show about the comprehensive of neutrophil gelatinase-associated lipocalin as a peredictor of pre-eclampsia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 143 articles, whereas the results of our search on SagePub brought up 24 articles. The results of the search conducted for the last year of 2014 yielded a total 70 articles for PubMed and 15 articles for SagePub. The result from title screening, a total 10 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: The utility of NGAL for diagnosing and assessing the severity of preeclampsia. The increase in NGAL due to preeclampsia is attributed to the presence of endothelium dysfunction and systemic inflammation.